Knowledge and Attitude Have No Correlation with Implementation of Breast Self Examination (BSE) - Winardi, Baksono; Novianty, Arini (Folia Medica Indonesiana, 2018)
This study aimed to know the existence of relationship between knowledge, attitude and implementation of BSE among midwifery students and mathematics students of Universitas Airlangga. This study used analytic observational method with cross-sectional approach. The sampling technique was the proportional sampling, consisting of 30 students of midwifery and 30 mathematics students. Analysis used was univariat and bivariat analysis with Spearman Rank. The significance level was 0.05 (5%). This study showed that 90% of midwifery students had good knowledge of BSE, 66.7% had sufficient attitude and 46.7% performed BSE in sufficient category. As many as 66.7% students of mathematics had sufficient knowledge about BSE, 63.4% had sufficient attitude and as many as 60% performed the BSE in the less category. The statistical test revealed p value = 0.267 for midwife respondents and 0.467 for mathematics respondents. Statistical test on the relationship between BSE attitude and implementation had p=0.100 for midwifery students and 0.407 for mathematics students. As a conclusion, there was no relationship of knowledge, attitude and implementation of BSE in the students of midwife and students of mathematics.